Alloying working surface during electroslag surfacing - V. G. Komkov; S. A. Gubar; G. G. Voskresensky (Омский научный вестник)
Parts subject to intense abrasive wear have a short service life. In the manufacture or restoration of such parts by electroslag surfacing, strengthening of the deposited metal is required. The use of ready-made alloying powders in surfacing increases the cost of the finished part, which necessitates the search for cheaper materials for alloying the parts being welded. The study of the efficiency of alloying the deposited metal through the melted insert, as well as by direct introduction of alloying powders into the slag bath has been carried out. Mixtures based on enriched mineral scheelite concentrate and graphite are used as alloying powders.